HUBUNGAN FAKTOR LINGKUNGAN DAN FAKTOR DEMOGRAFI DENGAN KEJADIAN DBD DI KOTA SALATIGA - Ika Tyas Prihartantie; Sulistyani Sulistyani; Nurjazuli Nurjazuli (Jurnal Kesehatan Masyarakat (Undip), 2017)
Dengue fever is one of public health problem because it is a disease with high fever and death score. Salatiga City consists of five subdistric as endemic of dengue fever that was still up and down. This research aims to analyze impact of environtment and demography that influence evidence of dengue fever in Salatiga City on 2013-2015. This research used obervational analitic approach with case control method to study restropectively of the causal characteristic. Population for this research is all household with dengue fever in Salatiga City during 2013 – 2015 totally 200 household. Data was collected with purposive sampling where each case group and control group was 100 household. Primary data wa collected by observation, checklist and interview whereas secondary data was from  Report of Subhead P2 Department of Health Salatiga City. Statictical analysis uses univariate, bivariate analysis with Chi Square Test (Significant level 0,05), and spatial analysis using ArcGis 9.3 software to describe the spread of Dengue fever according to the coordinate. The spread of dengue fever are around government center (2013) to be around main road in the middle of Salatiga (2014) and then almost near ring road from  center to Ambarawa City (2015). There is no significant correlation between  public facility around 50 m with dengue fever in Salatiga (p-value mosque 0,270;  shopping complex; 0.641;  factory 0.64); no significant correlation betweem existing Aedes aygepty larva at breding place inside or outside house with dengue fever in Salatiga (p-value bathing tub 0.452; larva at water jar 0.056; pail 0.596; water butt  0.321); no significant correlation between existing decorated plans in the house with dengue fever in Salatiga (p-value 0.280); no significant correlation between  the number of family member who live in the same house with dengue fever in Salatiga (p-value 1); no significant correlation between type of housing unit with dengue fever (p-value 0367).